Strategies to Enhance the Performance of Electrochemical Capacitors Based on Carbon Materials - Salinas-Torres, David; Ruiz-Rosas, Ramiro; Morallón, Emilia; Cazorla-Amorós, Diego (Frontiers in Materials, 2019)
The increasing worldwide energy consumption has contributed to both the vast growth of greenhouse emissions from carbon-containing fuels-based sources (coal, petroleum, etc.) and the depletion of the aforementioned sources. Given this scenario, the development of inexpensive and high-performing energy storage devices, which have the least possible environmental impact, is needed. At this point, electrochemical capacitors (ECs) or supercapacitors are a particular alternative or complementary option to batteries and fuel cells (FCs). ECs present high power output and long cycle life, but little power density compared to conventional or Lithium-ion batteries. Therefore, ECs are going to play a pivotal role, not only in portable electronic devices, but also to provide power density in hybrid electric vehicles. Many efforts have been focused on improving the energy output of ECs, although its enhancement keeping the high power density is still the cornerstone of most investigations. Many studies have been conducted towards the development of electrode materials such as metal oxides, conducting polymers or novel carbons. Nevertheless, they have shown important shortcomings to be implemented (i.e. high cost, low electrical conductivity, poor stability, etc.). Recent studies put the spotlight on nitrogen-containing carbon materials as candidates to improve the ECs performance in terms of energy. Optimizing the ECs configuration (asymmetric and hybrid) is another approach reported to tackle the challenge. Additionally, it is important to mention that the design of carbon materials obtained from inexpensive precursors lately attracted the attention of the research community. This review compiles works performed in our research group over the last years. The effect of nitrogen groups present in the carbon network on the capacitance will be reported and the study of asymmetric configuration to enhance de energy density will be discussed, either opening the potential window or by increasing the capacitance. Moreover, a lignin-based ECs will be described as an environmentally friendly approach. Finally, perspective and conceivable research guidelines in order to hurdle the challenges proposed to implement the carbon materials in the field of ECs will be addressed.